6B.05: SALT-SENSITIVITY OF ANGIOGENESIS INHIBITION-INDUCED BLOOD PRESSURE (BP) RISE. (June 2015) - Lankhorst, S.; Severs, D.; Marko, L.; Rakova, N.; Titze, J.; Müller, D.N.; Danser, A.H.J.; van den Meiracker, A.H.
Abstract : Objective: Angiogenesis inhibition with the VEGF-inhibitor sunitinib, an established anti-cancer therapy, induces hypertension and proteinuria. Exposed to osmotic stress, the Mononuclear-phagocyte-system cells produces VEGF-C and exert homeostatic regulatory activity by promoting lymphatic Na+ drainage; interference with this process resulted in salt-sensitive hypertension. Therefore, we hypothesized that sunitinib via blockade of the VEGF pathway leads to Na+ accumulation in the skin and salt-sensitive hypertension. Design and method: In male WKY rats, mean arterial pressure (MAP) was monitored telemetrically during oral treatment with sunitinib (7 mg/kg.day, n = 4–8) or vehicle (n = 4–8) after a normal salt diet (NSD: 0.5–1.0% NaCl and tap water) or a high salt diet (HSD: 8% NaCl and saline water) for 2 weeks. After 8 days of sunitinib or vehicle administration, 24-h urine was collected. After sacrificing, blood was collected for biochemical measurements and skin for Na+ concentration ([Na+]) using dry-ashing. Results: MAP during NSD was 101 ± 0.9 mmHg. HSD increased MAP by 27 ± 3 mmHg (P < 0.05 vs. NSD). Sunitinib increased MAP by 16 ± 1 mmHg during NSD (P < 0.05 vs. NSD alone) and by 23 ± 4 mmHg during HSD (P < 0.05 vs. HSD alone). Although body weight, serum [Na+] and plasma [cystatin-C] did not change in response to HSD and/or sunitinib, skin [Na+] increased from 89 ± 1 (NSD) to 92 ± 3 (HSD), and 97 ± 3 mmol/L (HSD+sunitinib), respectively (P < 0.03 for linear trend). Plasma endothelin-1 (ET-1) increased from 0.4 ± 0.09 (NSD) to 0.8 ± 0.05 pg/mL during HSD, and remained elevated with sunitinib. Skin [Na+] correlated both with MAP (r = 0.76, P < 0.01) and plasma ET-1 (r = 0.53, P < 0.05). Compared to NSD, proteinuria and endothelinuria increased during HSD, rising further (P < 0.05) with sunitinib. Conclusions: Angiogenesis inhibition-induced hypertension is salt-sensitive. The parallel increases in BP and skin [Na+], in the face of unaltered serum [Na+] and body weight, support the existence of a Na+-buffering compartment in the skin that may contribute to the salt-dependent volume and BP homeostasis during VEGF inhibition. Our data indicate that ET-1 may play a causal role in this phenomenon.